ANALYSIS OF SILDENAFIL AND ITS DERIVATIVES IN JAMU (HERBAL MEDICINES) USING LC/MS/MS SPECTROSCOPY - Rina Kurniaty; Khairan Khairan; Lelifajri Lelifajri (Universitas Syiah Kuala, 2018)
Jamu (herbal medicine) is a traditional Indonesian medicine used to nourish, treat, and restore of health, as well as for beauty and fitness. A healthy Jamu is safe when consumed and free from chemicals (in Indonesia it’s called BKO). BKO is a medicinal chemical compound which is intentionally added in jamu (herbal medicine), which aims to increase the accelerate effects of Jamu or herbal medicine from the usual. The aims of this study are to extract, isolate, identify and elucidate the structure of the BKO of sildenafil and it’s derivatives in two herbal preparations circulating in the city of Banda Aceh. Extraction, isolation and identification of sildenafil BKO and its derivatives in jamu were done by using column chromatography (CC) and thin layer chromatography (TLC) meanwhile, the structure elucidation of sildenafil and it’s derivatives were done by Fourier-Transform Infra-Red (FT-IR) and liquid chromatography/mass spectroscopy (LC/MS/MS). The results of extraction, isolation and identification with a solvent ethyl acetate: methanol: ammonium hydroxide (25%) (100: 15: 1.5 v/v showed that two jamu circulating in Banda Aceh positively contained BKO sildenafil derivatives, namely thiosildenafil. The FT-IR analysis showed a strong absorption of thiocarbonyl (C=S) group at 1288-1242 cm-1, which is a typical uptake of the thiosildenafil compound. The Spectroscopy LC/MS/MS analysis using electron spray ionization (ESI-MS/MS) showed that the isolate have a similar spectra with thiosildenafil compound [TSLD+H]+ at 491 m/z and [TSLD+Na]+ at 513 m/z and other derivate of thiosildenafil, namely propoxyphenylhydroxylethylthiosildenafil [PHTSLD+H]+ at 533 m/z.